Review of retrofitting techniques of deteriorated reinforced concrete columns - Kadhim, N J; Al-Ramahee, M A (IOP conference series. Earth and environmental science, 2023)
To ensure sustainability, all types of building structures should be kept in accepted condition throughout their life of service. Rehabilitation has been the subject of extensive research recently because of rising spending on construction and maintenance of constructed infrastructure. The most recent methods to reinforce current reinforced concrete columns, including both conventional and cutting-edge strengthening procedures, are presented in this study. Frequently, general materials used in repairing on-service reinforced concrete columns are concrete, steel, and different kind of Fiber Reinforced Polymer (FRP) composites. Conventional methods and procedures for different mode of failures strengthening, including all types of FRP procedures Near Surface Mounting (NSM) reinforcement, Externally Bonded (EB) FRP, and textile reinforced concrete will all be included in the discussion, and FRP pre-stressing methods for modifying existing structures.